Analisis Usability dan Aksesibilitas Desain UI/UX Aplikasi HIMAKOM Universitas Universal Menggunakan System Usability - Kaharuddin; Adam, Steffi; Pernando, Yonky (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
In the current era of advances in information technology, optimal UI/UX planning is crucial for producing a well-structured information system. A focus on user interface (UI) and user experience (UX) is important in ensuring the effectiveness and suitability of applications to user needs. Therefore, this research aims to analyze the Usability and accessibility aspects of UI/UX design designed with the Neumorphism design style, especially to meet the organizational needs of the Computer Faculty Student Association (HIMAKOM) at Universal University. The user-centered design (UCD) method is used in the application interface design process, with Usability testing using the System Usability Scale (SUS) as an evaluation tool. The research results show that although UI/UX design obtained an average SUS score of 67.4, which indicates a slight level of acceptability, it is still included in the marginal high category. These results indicate that the design requires adjustments to improve the overall user experience. However, in terms of accessibility, the design shows feasibility with an average percentage value of 76, indicating adequate attention to user diversity. In conclusion, although the UI/UX design requires several improvements to increase its Usability level, the design has sufficiently paid attention to the accessibility aspect, so it can be considered feasible and able to meet the needs of the HIMAKOM organization. It is recommended to carry out continuous iteration based on user feedback to improve optimal user experience. Thus, this research can provide important guidance for the development of applications that can best meet user needs and preferences